Impact of quarter report announcement on stock price: evidence from Malaysia stock market / Syamsyul Samsudin ... [et al.] - Samsudin, Syamsyul; Mustafa, Nik Nur Shafika; Hamzah, Nor Haliza; Mahmood, Che Khalilah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2019)
This research investigates the impact of Quarter Report Announcement towards stock price. Some investors believe that by referring to the quarterly announced dividend, they can predict the company performance and the stock price movement. However, does it necessarily true that an increase in the quarterly dividend announcement will cause the stock price to increase? Therefore, the researcher aims to answer this question by using variables such as revenues, profit before tax, met income, net intangible assets, earning per share and dividend as dependent variables. The data of public listed companies is collected from the Kuala Lumpur Stock exchange (KLSE). The study focuses on top ten gain companies in Malaysia based on their market capitalization. By applying the Panel Ordinary Least Square (POLS) based on 2013 until first quarter of 2018. The findings showed that all variables are significant and will give impact towards stock price while revenue is insignificant. It is because investors tend to believe that a company with high earning is stable and can earn more profit in future. The investors can look into the elements of Quarter Report Announcement before making investment decisions.